Keterbukaan Informasi Publik Terhadap Transparansi Penyaluran Zakat Pada BAZNAS Tangerang Selatan - Mas Sripah Nuraziza; Nur Izzah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the practice of transparency in zakat distribution by the National Zakat Agency (BAZNAS) of South Tangerang City and its compliance with Law Number 14 of 2008 concerning Public Information Disclosure. The method used is qualitative research with a normative juridical approach, including observation and focused interviews with relevant BAZNAS officials. The main findings indicate that BAZNAS of South Tangerang City has implemented a structured and accountable zakat distribution system, in accordance with applicable legal provisions. However, published performance reports are still inconsistent and there are deficiencies in the preparation of official public information lists. The study's conclusions indicate that although transparency in zakat distribution has been running well, improvements in the aspect of published information are needed to strengthen accountability and public trust. The implications of this study highlight the importance of more systematic public information management to support the effectiveness of zakat management.